2009
DOI: 10.1073/pnas.0904863106
|View full text |Cite
|
Sign up to set email alerts
|

ChIP-Seq of transcription factors predicts absolute and differential gene expression in embryonic stem cells

Abstract: Next-generation sequencing has greatly increased the scope and the resolution of transcriptional regulation study. RNA sequencing (RNA-Seq) and ChIP-Seq experiments are now generating comprehensive data on transcript abundance and on regulator-DNA interactions. We propose an approach for an integrated analysis of these data based on feature extraction of ChIP-Seq signals, principal component analysis, and regression-based component selection. Compared with traditional methods, our approach not only offers high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
349
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(369 citation statements)
references
References 39 publications
16
349
2
Order By: Relevance
“…edu). As a key distinction from other algorithms integrating gene expression and TF ChIP-seq data (15)(16)(17)(18), RABIT better captures the properties of cancer cells, such as CNA and DNA methylation, that shape tumor gene expression independently from TF regulation. Additionally, somatic mutations of the TF-coding region can perturb transcriptional regulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…edu). As a key distinction from other algorithms integrating gene expression and TF ChIP-seq data (15)(16)(17)(18), RABIT better captures the properties of cancer cells, such as CNA and DNA methylation, that shape tumor gene expression independently from TF regulation. Additionally, somatic mutations of the TF-coding region can perturb transcriptional regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, there are abundant previous works on integrating ChIP-seq and gene expression data to understand gene regulatory mechanisms (15). For example, ChIP-seq profiles of 12 TFs and RNA-seq expression profiles in mouse embryonic stem cells have been analyzed together, using the regression method (16)(17)(18). However, these previous studies were conducted when ChIP-seq and expressionprofiling data were generated in the same condition, without further requirement of removing any background confounding effect.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this hypothesis, clusters of transcription factor binding sites have been used to identify novel enhancers (Berman et al 2002;Markstein et al 2002), a method that is particularly powerful when combined with sequence conservation (Kazemian et al 2010), and which has proved useful even in the absence of experimentally determined transcription factor binding specificities ). Many, although not all, regions bound in vivo by multiple transcription factors confer enhancer activity and drive gene expression (Chen et al 2008;Ouyang et al 2009;Zinzen et al 2009;Negre et al 2011). However, the mechanisms underlying these overlapping patterns of binding remain incompletely understood.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…27 Several general approaches have been proposed to identify TFs acting as key players 28 in gene regulation depending on the available data: Coexpression analysis combined 29 with computational predictions of TF sequence binding can be used to identify key 30 TFs [18]. Genome-wide TF binding data, as produced by TF ChIP-seq, is widely used 31 to identify important TFs: ChIP-seq data was incorporated into coexpression 32 analysis [43], was combined with transcriptome data [49,66], used for the construction 33 of Gene Regulatory Networks (GRNs) [8], and used together with Hi-C data [40].…”
mentioning
confidence: 99%
“…It was shown that using 47 DNaseI-seq data alone can lead to highly accurate TF binding predictions [13,51], 48 therefore we mainly focus on open-chromatin data in this article. 49 There are two general classes of methods to predict TF binding: site-centric 50 methods [13,32,42,51,57,69], and segmentation-based methods [3,7,24,25,27,48,50,58]. 51 Site-centric methods require the identification of putative TF binding sites (TFBS) 52 using TF binding motifs represented with position weight matrices (pwms).…”
mentioning
confidence: 99%